Use of complementary medicine products: a nationally representative cross-sectional survey of 2019 Australian adults. Issue 7 (16th July 2019) - Harnett, Joanna E; McIntyre, Erica; Steel, Amie; Foley, Hope; Sibbritt, David; Adams, Jon
Abstract : Objectives: To provide a contemporary description of complementary medicine (CM) product use in Australia. Design: Cross-sectional survey. Setting: Online. Participants: A nationally representative sample (n=2019) of the Australian adult population. Primary and secondary outcome measures: Primary outcomes measures included the use and type of CM products used, and source of recommendation. Secondary measures included disclosure of CM product use to health practitioners, concomitant use of pharmaceuticals and predictors of use. Results: Prevalence of CM product use was 50.3%, with the most frequently used being vitamin and mineral supplements (VMSs; 47.8%) and homoeopathic medicines the least used (6.8%). A majority of respondents using CM products were also using pharmaceutical products, and small but significant associations were found between the use of CM products and pharmaceuticals (p<0.05). Small statistically significant associations were found between use of vitamin products and disclosure of use to general practitioners (GPs; Cramer's V=0.13, p=0.004) and hospital doctors (Cramer's V=0.11, p=0.04), and between use of herbal medicines and disclosure to both GPs (Cramer's V=0.11, p=0.02) and hospital doctors (Cramer's V=0.12, p=0.03). Women, those with higher education and those with no private health insurance were more likely to use CM products (p<0.05), while those without chronic conditions were less likely to use CM products (p<0.05) (χ 2 (29)=174.70, p<0.001). Conclusions: The number of Australians using CM products has remained relatively stable and substantial for nearly two decades. The majority of CM use relates to VMSs. Given the number of Australians using both CM products and pharmaceutical medicines, it is important to evaluate the potential clinical implications of such practices to ensure safe, effective and coordinated health policy and patient care.